Some Biological Compounds, Antioxidant and Antimicrobial Activities of Endemic Hypericum uniglandulosum - Turkoglu, Semra; Turkoglu, Ismail; Celik, Sait; Bahsi, Muammer; Gur, Seher; Parlak, Akif Evren (Springer, 2015)
We stadied some biologically active compounds, radical scavenging capacities, and antimicrobial activities in Hypericum uniglandulosum extracts. It was found that palmitic acid (12.16 +/- 0.69%), oleic acid (3.45 +/- 0.17%), and alpha-linolenic acid (17.15 +/- 0.84%) were the dominant fatty acids in the extracts. It was concluded that the extracts contained stigmasterol (52.60 +/- 0.57 mu g/g), alpha-tocopherol (29.2 +/- 0.54 mu g/g), cholesterol (66.16 +/- 0.78 mu g/g), and as well as beta-sitosterol (289.33 +/- 4.96 mu g/g). It was also determined that the methanol extracts were the most effective against free radicals. The results of the present study show the potent antimicrobial activity of H. uniglandulosum constituents suggesting that they deserve further consideration as novel antibacterial agents.
Keywords: Hypericum uniglandulosum; antioxidant; antimicrobial; vitamins; fatty acids